2014
DOI: 10.1177/0269216314545802
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of measurement equivalence of the Family Satisfaction with the End-of-Life Care in an ethnically diverse cohort: Tests of differential item functioning

Abstract: Background The Family Satisfaction with End-of-Life Care is an internationally used measure of satisfaction with cancer care. However, the Family Satisfaction with End-of-Life Care has not been studied for equivalence of item endorsement across different socio-demographic groups using differential item functioning. Aims The aims of this secondary data analysis were (1) to examine potential differential item functioning in the family satisfaction item set with respect to type of caregiver, race, and patient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
(57 reference statements)
0
8
1
Order By: Relevance
“…Although there is no literature on the FAMCARE in a sample of Hispanic caregivers to persons with ADRD, earlier work on ethnically diverse caregivers may have informed the hypotheses. In contrast to the findings reported here, in an earlier paper on DIF in the FAMCARE (Teresi et al, 2015), Black responders reported less satisfaction with their care, conditional on the trait.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although there is no literature on the FAMCARE in a sample of Hispanic caregivers to persons with ADRD, earlier work on ethnically diverse caregivers may have informed the hypotheses. In contrast to the findings reported here, in an earlier paper on DIF in the FAMCARE (Teresi et al, 2015), Black responders reported less satisfaction with their care, conditional on the trait.…”
Section: Discussioncontrasting
confidence: 99%
“…However, in an earlier study a similar item, "Satisfaction with the patient's pain relief" was found to show DIF for the comparison of Blacks and White non-Hispanics. In that study, it was found that conditional on the satisfaction level, caregivers of Black patients were less satisfied with pain relief (Teresi et al, 2015), a finding corresponding to findings of racial and ethnic disparities in pain treatment identified by Green et al (2003). It is possible that the content experts posited the presence of an unmeasured secondary extraneous factor such as personal experiences that may have influenced responses to satisfaction items.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Earlier psychometric studies of the FAMCARE identified varying factor structures. One study using IRT examined the performance of items in terms of information and differential item functioning between Black and White subsamples (Teresi et al, 2015). Because of overlapping category response functions identified in the prior analyses, the response categories were collapsed from five into three: very satisfied responses coded as 2, satisfied coded as 1, and indecision or dissatisfaction coded as 0.…”
Section: Methodsmentioning
confidence: 99%
“…Areas of difference included patient's pain relief, information provided about prognosis, referrals to specialists, the way treatments were performed, inclusion of the family in treatment decisions, and information given about tests. 46 Research can address gaps through development and testing of culturally adapted models of care. For example, in a study of African Americans coping with cancer, participants reported that an interactive communication intervention which facilitated Afrocentric coping skills such as relying on faith, promoting fictive kin support, highlighting positives, and encouraging flexibility in family roles resulted in significantly improved family member communication and satisfaction.…”
Section: Ethnic and Cultural Differencesmentioning
confidence: 99%